STRATEGI PENGEMBANGAN KETERAMPILANPROBLEM SOLVING DALAM KONTEKS MEMBANGUNDISASTER RESILIENCE - Utaminingsih, Diah; Abdurrahman, Abdurrahman; Kadaryanto, Budi; Maulina, Hervin (FKIP Universitas Lampung, 2016)
Problem Solving Skills Development Strategies in The Context of Building Disaster Resilience. This study will provide an alternative strategy that can be done to improve problem solving skills, on children in the context of building the disaster resilience which are integrated in the learning process of science through community learning strategy. Qualitative and psychosocial research ethnography was conducted on 34 students in the District of the West Coast as the area with the most potential to experience the devastating earthquake and tsunami. Data were obtained using a strategy of focused group discussions and depth interviews with elements of the school community which are teachers, and parents. The purpose of the involvement of the school community was to get the data in understanding the resilience of students. The research proved that resilience is at the levels which are still low and this condition further provide recommendations related to alternative strategies for the development of higher level thinking skills for students in disaster prone areas. Keyword: problem solving skills, disaster resilience, elementary school students, school community DOI: http://dx.doi.org/10.23960/jpp.v6.i1.201601